2022
DOI: 10.1007/s12094-022-02832-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of tumour stroma in regional lymph node metastases in colorectal cancer patients: a theoretical framework for future diagnostic imaging with FAPI PET/CT

Abstract: Purpose The recently developed fibroblast activation protein inhibitor (FAPI) tracer for PET/CT, binding tumour-stromal cancer-associated fibroblasts, is a promising tool for detection of positive lymph nodes. This study provides an overview of features, including sizes and tumour-stromal content, of lymph nodes and their respective lymph node metastases (LNM) in colorectal cancer (CRC), since literature lacks on whether LNMs contain sufficient stroma to potentially allow FAPI-based tumour dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…and peritoneal implants (100.0% vs. 55.0%). Regarding the detection of lymph nodes and distant metastasis, N and M stages are crucial for the treatment and prognosis of patients with CRC [29,30]. In our study, there were no signi cant differences in the FAPI PET parameters among patients with different N and M stages.…”
Section: Relationship Between T Stage and Fapi Parameters In Crcmentioning
confidence: 42%
See 1 more Smart Citation
“…and peritoneal implants (100.0% vs. 55.0%). Regarding the detection of lymph nodes and distant metastasis, N and M stages are crucial for the treatment and prognosis of patients with CRC [29,30]. In our study, there were no signi cant differences in the FAPI PET parameters among patients with different N and M stages.…”
Section: Relationship Between T Stage and Fapi Parameters In Crcmentioning
confidence: 42%
“…The SUVmax thresholds(30, 40, 50, and 60%) and SUVmean thresholds(30, 40, and 50%) in patients with stage T4 tumors were higher than those in patients with stage T3 tumors. Furthermore, the tumor SUVmean 30% in our analysis can be reliably applied in future studies.…”
mentioning
confidence: 81%
“…The intricate and dynamic tumor–stroma crosstalk has been observed to include the cancer-associated fibroblasts as important players, potentially also enabling the seed-and-soil principle of Paget and causing stromal metastases in lymph nodes. 14 , 33 The TSR can be scored on these metastases as well, and patients with stroma-high primary tumors and stroma-high lymph node metastases have been observed to have the worst survival. 34 , 35 Even small lymph nodes ≤5 mm in diameter, during routine radiologic imaging not suspected of malignancy, can contain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring the TSR in lymph nodes in the future, as well as more research on improving positive lymph node detection, is pertinent for an even more tailored treatment. 33 …”
Section: Discussionmentioning
confidence: 99%
“…A study of 28 cases of malignant tumors in the lower digestive tract showed for the first time that FAPI showed high uptake and good TBR in primary and metastatic colorectal cancer lesions, which further changed the clinical stage of TNM in related patients and improved target volume delineation [ 46 ]. For the lymph node metastasis of colorectal cancer, the present research shows that there are many stroma in the lymph nodes and corresponding lymph node metastases (LNM) of CRC, which indicates that FAPI PET/CT may improve the identification of lymph node metastases of CRC [ 47 ].…”
Section: Fapi Pet/ct Imagingmentioning
confidence: 99%